From socialization to self-socialization? Exploring the role of digital media in the religious lives of young adults in Ghana, Turkey, and Peru. Issue 2 (3rd April 2019) - Moberg, Marcus; Sjö, Sofia; Golo, Ben-Willie Kwaku; Erdiş Gökçe, Habie; Hart, Rafael Fernández; Cardenas, Sidney Castillo; Benyah, Francis; Jó, Mauricio Javier Villacrez
ABSTRACT: Previous research has pointed to the central role of media for the current young adult generation when it comes to finding information about religion, exploring beliefs, and developing a religious identity. This article explores how young adult university students in three different contexts – Ghana, Turkey, and Peru – report using digital media for religious purposes. The article builds on previous research on the role of media in religious socialization and explores the usefulness of the notion of self-socialization in a transnational study. The studied contexts are all shown to differ when it comes to levels of self-reported religiosity and use of media for religious purposes. The article illustrates the independent use of digital media in all contexts and self-socialization taking place on a general level, but also highlights the continuous importance of traditional socialization agents, thus questioning simplistic understandings of the role of media in religious socialization.